Factors Contributing to The Maintenance of The Inge Ndai Language in The Family in Sambori Village - Ardila, Rahmatia; Rokhman, Fathur; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Bima, West Nusa Tenggara, features a diverse range of languages. The range of languages spoken by the Bima people in Sambori Village, Lambitu District, demonstrates the presence of bilingual and multilingual speakers. This research aims to investigate the elements that contribute to the survival of the Inge Ndai language in the family realm in Sambori Village. The listening approach was employed in this study. The listening approach employs (1) fundamental tactics in the form of tapping techniques and (2) advanced techniques, namely: listening to free involvement and conversation (SBLC), recording, and taking notes. The equivalent procedure is used during the data analysis stage. The matching procedure is carried out in two stages, namely: (1) a fundamental technique in the form of a determining element sorting technique (PUP), and (2) a more advanced technique in the form of an equalizing comparison technique (HBS). In this study, the outcomes of data analysis are presented in a written report. According to the study's findings, the following elements contribute to the survival of the Inge Ndai language in the family realm in Sambori Village: loyalty factors, language pride factors, awareness factors for language norms, age factors, and work factors.